(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe the current status of tuberculosis service availability and readiness and some associated factors in commune health stations, Nghe An province in 2023. Subject and methods: A cross-sectional descriptive was conducted on 401 out of 460 commune health stations in Nghe An province. Results: The results of the study showed that more than 90% of the commune health stations participating in the study were in the countryside (57.61%) and the mountainous (32.34%). Only 74.12% of the commune health stations had doctors and 39.65% had tuberculosis diagnosis, while the most common diagnosis method in commune health stations in Nghe An province is clinical signs observation (98.74%). The medicine availability in 3 areas was low and the differences between the areas were statistically insignificant. Conclusions: There are some limits in workforce, diagnosis, treatment, facilities, biological products and medicines in the current status of tuberculosis service availability and readiness.